2013
DOI: 10.1016/j.apenergy.2012.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Electric storage in California’s commercial buildings

Abstract: Most recent improvements in battery and electric vehicle (EV) technologies, combined with some favorable off-peak charging rates and an enormous PV potential, make California a prime market for electric vehicle as well as stationary storage adoption. However, EVs or plug-in hybrids, which can be seen as a mobile energy storage, connected to different buildings throughout the day, constitute distributed energy resources (DER) markets and can compete with stationary storage, onsite energy production (e.g. fuel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 22 publications
0
42
0
2
Order By: Relevance
“…As previous DER-CAM investigations have shown the tariff structure and in particular the rates imposed on power demands have a strong influence on the optimal behavior and configuration of DER installations [21][22][23] Tariffs with high on-peak energy rates and on-peak demand charges create opportunities for economic savings from load shifting. An investigation of a large religious building in Saudi Arabia found that the absence of tariff demand charges significantly reduced the economic feasibility of chilled water TES systems, despite a large disparity between on-peak and off-peak cooling consumption [24].…”
Section: Electricity Tariffmentioning
confidence: 99%
“…As previous DER-CAM investigations have shown the tariff structure and in particular the rates imposed on power demands have a strong influence on the optimal behavior and configuration of DER installations [21][22][23] Tariffs with high on-peak energy rates and on-peak demand charges create opportunities for economic savings from load shifting. An investigation of a large religious building in Saudi Arabia found that the absence of tariff demand charges significantly reduced the economic feasibility of chilled water TES systems, despite a large disparity between on-peak and off-peak cooling consumption [24].…”
Section: Electricity Tariffmentioning
confidence: 99%
“…Site-specific inputs to the model are pre-optimization end-use energy loads, detailed electricity and natural gas tariffs, and DG investment options [31]. Figure 2 shows a high-level schematic of all building energy flows modeled in DER-CAM.…”
Section: Parametersmentioning
confidence: 99%
“…Likewise, various studies [7][8][9][10][11] have reported ability of storage to further support system operation and thus renewables integration through provision of network services such as congestion management in transmission and distribution systems. In the particular case of distributed storage, various references have demonstrated [12][13][14][15] how design of distributed energy systems can be improved by increasing participation of storage, which enhances system flexibility and facilitates integration of further distributed energy resources such as distributed generation (e.g. solar and wind).…”
Section: Literature Review and Contributionmentioning
confidence: 99%